2013
DOI: 10.1177/0969141313505747
|View full text |Cite
|
Sign up to set email alerts
|

Updating Diabetic Retinopathy Screening Lists using Automatic Extraction from GP Patient Records

Abstract: Objectives: Diabetic Retinopathy screening services aim to reduce the risk of sight loss amongst patients with diabetes. The rising incidence of diabetes in England and the operational need to ensure the accuracy and timeliness of screening lists led to a pilot study of electronic extraction of data from primary care. This study aimed to evaluate the effectiveness of updating the single collated list of patients eligible for diabetic eye screening using extracts from electronic patient records in primary care.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…9. We have previously shown (outside this project) that there are patients with diabetes unknown to screening programmes and that some of these have referable DR. 52 This project has shown that GP2DRS or similar software to extract demographic and risk factor data from primary care is necessary. 10.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…9. We have previously shown (outside this project) that there are patients with diabetes unknown to screening programmes and that some of these have referable DR. 52 This project has shown that GP2DRS or similar software to extract demographic and risk factor data from primary care is necessary. 10.…”
Section: Resultsmentioning
confidence: 99%
“…A detailed investigation was carried out into the reasons why these patients were not known to Gloucestershire DESP. 52 2. Over the subsequent 12 months, we sent out patient information leaflets to practices in Gloucestershire, and we obtained risk factor data by September 2010 on 4220 people with diabetes by means of a single letter sent after screening at a practice asking that practice to provide a consent code update.…”
Section: Proposed Time Period For Retention Of Relevant Documentationmentioning
confidence: 99%
See 1 more Smart Citation
“…98,99 Automated interrogation and extraction of electronic primary care data may identify additional candidates for screening. 100…”
Section: Changes To Dr Screening Service Deliverymentioning
confidence: 99%